Factors affecting the choice of climate change adaptation strategies of Mango Farmers in Island Garden City of Samal, Davao del Norte - Banguis, Eloisa Lynne P.
One of the pressing issues in international discussions is the threat brought by the continuously changing climatic patters. Climate has been perceived to be the primary determinant of agricultural productivity. In order for the farmers to build resilience and lessen the possible threat of climate change, there is urgency for the farmers to implement climate change strategies. To identify the factors affecting the choice of adaptation strategies of the mango farmers , the Multivariate Probit (MVP) Regression Analysis was used. A cluster analysis was also done to group the farmers based on their adaptive level. The collection of data was done through a focused group discussion and personal interviews using a survey questionnaire. A total of 160 respondents were interviewed. Findings show that majority of the respondents (78.8%) have very high awareness of climate change. The results of the cluster analysis also show that the low adaptive cluster mostly consists of farmers who have very high awareness on climate change and at the same time are those with m those whose main source of income came from non-farm livelihood, have below Php 5,000 and have attended few to non mango related trainings. Furthermore, annual incomes from mango farming, main source of income, household size, presence of excessive rain, presence of drought, presence of pests and diseases, access to production extension, and access to credit were found to be the significant factors that affect the farmers? decision to adapt. Increasing the level of awareness through a community-based information system is one of the recommended interventions.